Government and (non)event: the promise of control. (17th February 2017) - Anderson, Ben; Gordon, Rachel
Abstract: Control rooms routinely deal with happenings that might become events. They attempt to hide events and their possibility from the users of infrastructure by undertaking various forms of action to stop events coming to pass. Based on ethnographic research in a motorway control room, in this paper we describe how events are grasped and handled and subject to the effect of control. Focusing on how the promise of control is provisionally achieved through detection–diagnosis–response work, we show how control room action is situated on the ambiguous line between event and non- or quasi-event and involves making happenings that might be or might become events into their opposite: non-events, or routine occurrences. We use the case of the work of control rooms in dialogue with Michel Foucault on the relation between 'government and event' and Lauren Berlant on 'modes of eventfulness' to challenge the emphasis on the event as dramatic transformation in some current research on securing life and some geographical work on events. Paying close attention to what control rooms do shows the multiplicity of relations between government and (non)event, and invites us to expand the 'modes of eventfulness' that social and cultural geographers learn to sense and disclose.